Pengaruh Suhu Permukaan Laut terhadap Curah Hujan di Pulau Bali Tahun 2009-2018 - Ida Bagus Agung Parahita Adiguna; I Wayan Nuarsa; Ni Luh Putu Ria Puspitha (Journal of Marine and Aquatic Sciences, 2021)
Change in sea surface temperature (SST) has a huge impact to rainfall intensity. This research analysed the trend of SST all over Bali island for 10 years (from 2009 to 2018) using MODIS satellite level 3, covered 7.8958oSouth -8.8958oSouth and 114.4791oEast - 115.6875oEast. The data for rainfall trend was collected from 12 rain observer stations of BMKG (Indonesian Meteorological, Climatological, and Geophhysical Agency). The statistical correlation between SST and rainfall intensity were analyzed using Microsoft Excel software. The result found that the SST in Bali ranged from 25.4oC until 31.5oC. The change of SST has a similar pattern to the monsoon cycle where the western monsoon is relatively warmer than the eastern monsoon. The rainfall trend in Bali is closely related to the monsoon cycle. During the western monsoon,the average monthly rainfall value in Bali is more than 150 mm, while the rainfall value on the eastern monsoon is slightly different, which is <150 mm. The correlation between SST and rainfall is influenced by the monsoon direction.The correlation between SST and rainfall in the west and transitional season Iis weak with a coefficient correlation value of -0,46 at lag 0, whereas in the east and transitional season II showed a strong correlation coefficient value of 0.94 in lag 0 (in the same month).